Control interno en el área de ventas y su incidencia en la rentabilidad en Dey-Mar el comisariato del marisco, cantón La Maná, provincia de Cotopaxi. - Faz Cáceres, Lorena Yamilex (2023)
The current research work was carried out in DEY-MAR, the seafood market which is located in La Maná canton, Cotopaxi province, where the activities were made by the students who participated in the research. According to this, it is evidenced that the work was developed in accordance with the investigations focused on books, magazines, bibliographic sources, etc. The general objective was to evaluate the Internal Control in the sales area and its impact on profitability and as a proposal, to elaborate a manual of political functions and procedures for the sales area. On the other hand, for the research work, quantitative research was used, as well as field research by applying surveys, questionnaires, and an observation sheet as tools. Based on the development and application of the internal control questionnaire, according to COSO I, it was possible to determine the percentage of HIGH confidence level at 87% and the level of LOW risk at 13%. It showed that the market has different shortcomings that are affecting the development and fulfillment of its goals, being the most relevant, the lack of a manual of political functions and procedures in which collaborators can carry out their daily activities in an adequate manner. It is important to mention that the market does not use financial indicators to identify the percentage of profitability to be obtained when developing its economic activity. Finally, a profitability analysis was developed through profitable indicators that resulted in a gross margin of 40%, operational profitability of equity of 11.88%, and an ROA of 5.16%. It was concluded that as a proposal of this research work, a manual of functions, policies and procedures had to be developed to improve the economic and labor activity in DEY-MAR, the seafood market.